(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the relationship between axial length and demographic factors as well as visual acuity in Vietnamese individuals aged 46-65 years. Subjects and methods: A cross-sectional descriptive study was conducted on 195 Vietnamese individuals aged 46-65 using the intraocular lens Master 700 device at the Vietnam National Eye Hospital. Results: Among 195 participants, there were 94 males (48.2%) and 101 females (51.7%). The mean axial length was 23.13 ± 0.66 mm. Axial length decreased with age and was significantly greater in males (p < 0.05). There was a positive linear correlation between axial length and visual acuity. Axial length and intraocular lens power did not significantly differ according to geographic location. Conclusion: Axial length is a valuable indicator in the diagnosis and treatment of various ocular conditions. This study provides axial length data specific to the Vietnamese population, contributing to the normative biometric database of the eye, serving as a reference standard for comparison with pathological cases.